The bridesmaid ebook Home to hickory hollow series, book 2. - Lewis, Beverly (Home to Hickory Hollow, 2012)
When distance, family hardships, and a forbidden desire threaten her secret courtship with outsider Eben Troyer, will Joanna ever be more than a bridesmaid?